Mechanism study on the treatment of ulcerative colitis by Gegen Qinlian nano-preparation through promoting M2 macrophage polarization - Li, Jilei; Cao, Jiarui; Zhang, Zhenyu; Wang, Sizhe; Zhu, Meng; Yang, Lili; Ouyang, Wenhui; Ma, Chunzheng (Frontiers in Molecular Biosciences, 2025)
ObjectiveTo address the core pathological features of intestinal barrier disruption and immune imbalance in ulcerative colitis (UC), we developed a nano-targeted formulation (GGQL nano-preparation) based on berberine, puerarin, baicalin, and glycyrrhizin by combining traditional Chinese medicine (TCM) and nanotechnology in this study. We aimed to investigate whether GGQL nano-preparation could promote M2 macrophage polarization, correct intestinal inflammation, and treat UC.MethodsWe used databases to identify M2 macrophage-related gene targets for GGQL nano-preparation in UC. Protein-protein interaction networks, topological analysis, and GO/KEGG enrichment analyses revealed GGQL nano-preparation‘s potential regulation of macrophage polarization via a specific pathway. We validated this using a dextran sulfate sodium (DSS)-induced UC model in C57BL/6 mice. Parameters assessed included the disease activity index (DAI), colon length, colitis macroscopic damage index (CMDI), spleen index, and pathological changes (via HE staining). Immunohistochemistry detected AMPK-PPAR axis factor changes to determine GGQL nano-preparation’s impact on M2 macrophage polarization and intestinal inflammation.ResultsOur analyses suggested the GGQL nano-preparation reduced the DAI, enhanced colon length, improved CMDI scores, and mitigated splenic inflammation. HE staining showed GGQL nano-preparation alleviated inflammation in the spleen, lungs, and colon. Immunohistochemical findings indicated GGQL nano-preparation upregulated AMPK, PPAR, and SIRT1 expression. Mechanistically, GGQL nano-preparation promoted M2 macrophage polarization through the AMPK-PPARγ axis, achieving therapeutic objectives for UC.ConclusionThe GGQL nano-preparation effectively promotes M2 macrophage polarization via the AMPK-PPARγ axis, treating UC.